GAP-43 is involved in the orientation of cell division by interacting with GΑI during neurogenesis. (1st February 2020) - Huang, Rui; Xiao, Hui; Zhao, Junpeng; Ju, Lili; Wen, Yujun; Xu, Qunyuan; Cui, Xiaodai
Abstract: Purpose: Recent studies have shown that growth-associated protein-43 (GAP-43) may influence the mitotic-spindle orientation of Madin-Darby Canine Kidney (MDCK) cells through interacting with G proteins in vitro. However, whether GAP-43 interacts with the G proteins under the influence of mitotic spindle positioning related to the orientation of cell division during neurogenesis remains unclear. In order to explore the molecular mechanism in vivo, the GAP-43 transgenic mice were produced and the angles of cell division in the ventricular zone (VZ) during neurogenesis (embryonic period between 13.5 and 17.5 days) were measured in both transgenic mice and wild type mice by spindle angle analysis. Materials and methods: The interaction of GAP-43 and Gαi was detected by co-immunoprecipitation (co-IP), whereas the localization of GAP-43 was determined by immunofluorescence. Results: The results obtained using co-IP and immunofluorescence showed that GAP-43 is localized on the cell membrane and interacts with Gαi. This interaction dramatically induced a significant increase in the proportion of horizontally and intermediately dividing cells during the embryonic period of 13.5 days in the transgenic mouse brain, as observed by spindle angle analysis. Conclusions: It can be concluded that GAP-43 is involved in the orientation of cell division by interacting with Gαi, and that this may be an important mechanism for neurogenesis in the mammalian brain.